Heart Sound Measurement and Analysis System with Digital Stethoscope - Haibin Wang; Jian Chen; Yuliang Hu; Zhongwei Jiang; Choi Samjin (2009 2nd International Conference on Biomedical Engineering and Informatics, 2009)
This paper focuses on the heart sound measurement and analysis system for in-home use of heart condition monitoring. The heart sound acquiring system includes a traditional chest-piece, an earphone, a microphone and an IC recorder. The recorded data transmitted into a computer by USB interface are analyzed by the analytical model of single degree-offreedom(SDOF) for extracting cardiac sound characteristic waveform(CSCW). Furthermore, the 4 characteristic parameters [T1, T2, T11, T12] related to the first heart sound (SI) and the second heart sound (S2) are defined by the time intervals between the crossed points of the CSCW and the threshold value (THV) line in order to discriminate normal and abnormal heart sounds. Meanwhile, an easy understanding graphical representation for these parameters is considered, so that inexperienced users are able to monitor their heart condition easily. Finally, the case study on 40 normal and 20 abnormal heart sounds from 10 healthy volunteers and 5 patients with heart disorders is carried out, the higher discrimination performances are achieved 92.5%, 95% in accuracy, respectively. The usefulness and efficiency of this proposed system and the CSCW method are demonstrated.